The polysaccharide–peptide complex from mushroom Cordyceps militaris ameliorates atherosclerosis by modulating the lncRNA–miRNA–mRNA axis. Issue 6 (28th February 2022) - Li, Yuan; Miao, Miao; Yin, Fan; Shen, Nuo; Yu, Wen-Qian; Guo, Shou-Dong
Abstract : An N-glycosidic polysaccharide-peptide complex CMPS-80 from the fruiting body of C. militaris modulates ceRNA network in the liver of apoE ( −/− ) mice. Abstract : An N -glycosidic polysaccharide–peptide complex CMPS-80 was obtained from the fruiting body of C. militaris . Of importance, CMPS-80 significantly ameliorated formation of atherosclerotic lesions and plasma lipid profiles in apolipoprotein E-deficient mice. Integrated informatics analysis suggested that CMPS-80 can modulate multiple lncRNA–microRNA–mRNA axes. CMPS-80 has a potential application for prevention of hyperlipidemia and atherosclerosis.